Anna Triandafyllidou (ed.): Irregular Migrant Domestic Workers in Europe: Who Cares? Aldershot: Ashgate 2013, 256 pp. - Ezzeddine, Petra (Lidé města, 2013)
A review of the book by Anna Triandafyllidou.